Optimization of amylase production from bitter manihot esculenta using Aspergillus Niger - Khalaf, Abubakir Ibraheem; Alam, Md. Zahangir (IIUM Press, International Islamic University Malaysia, 2017)
Amylases are industrial enzymes which hydrolyze carbohydrate molecules to give diverse products including dextrins and progressively smaller polymers composed of glucose units. Due to their wide industrial applications, these enzymes account for 65 % of global enzyme market with microorganisms being the predominant sources for enzyme production. Enzyme production on industrial level is still faced by challenges represented by high production costs, selection of appropriate microorganisms and improvement of medium composition and process condition parameters. Hence, the search is always on for means to decrease enzyme production costs and increase enzyme productivity.